2022
DOI: 10.2174/18744346-v16-e2209261
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Cost-Effectiveness of Plastic Surgery Based on the Satisfaction with Quality of Life and Nasolabial Appearance in Thai Preteens with Cleft Lip and Palate

Abstract: Background: Cleft Lip and Palate (CLP) negatively affect the quality of life (QoL) and nasolabial appearance, especially in preteen patients who start to be interested in their own appearance and society. Objective: The objective of this study is to evaluate the cost-effectiveness of plastic surgery for Thai preteen CLP patients through their satisfaction with their QoL and nasolabial appearance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…In 1991, the aesthetic assessment was used to evaluate the index of the aesthetic of the lip and the nose by Asher-McDade et al 12 It has become widely used and found reliable when assessed by experienced medical professionals and the general public. 13 , 16 19 This research study, which examined the aesthetic assessment by Asher-McDade in 32 unilateral and bilateral complete CLP patients, showed that the experienced evaluators had scored at the “fair” level with a high inter-rater in all three aspects and with statistical significance (Cronbach’s alpha coefficient 0.69–0.76, p < 0.01).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In 1991, the aesthetic assessment was used to evaluate the index of the aesthetic of the lip and the nose by Asher-McDade et al 12 It has become widely used and found reliable when assessed by experienced medical professionals and the general public. 13 , 16 19 This research study, which examined the aesthetic assessment by Asher-McDade in 32 unilateral and bilateral complete CLP patients, showed that the experienced evaluators had scored at the “fair” level with a high inter-rater in all three aspects and with statistical significance (Cronbach’s alpha coefficient 0.69–0.76, p < 0.01).…”
Section: Discussionmentioning
confidence: 88%
“…In that study, it was found that the satisfaction scores by the experienced experts had been high 12 or even higher. 19 , 22 24 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations